Evaluasi Pengembangan Kawasan Minapolitan di Kecamatan Blanakan Kabupaten Subang Tahun 2013-2018 - Iin Rohayah; Mulyo Hendarto (Universitas Diponegoro, 2020)
This study’s aims are: (1) to analyse the development of production in Blanakan District before and after the existence of the Minapolitan area; (2) to analyse the development of supporting facility in the Minapolitan Area of subdistrict Blanakan; (3) to analyse the development of fisheries processing in the Minapolitan Area of subdistrict Blanakan; (4) to analyse the development of fisheries marketing in the Minapolitan Area of subdistrict Blanakan. This study used description and crosstabulation analysis. Then qualitative analyze taken from interpretation of data by giving information and explanation. The result shows that the evaluation of the supporting facility in the Minapolitan Area is 65.02% is categorized as less undeveloped. Minapolitan supporting infrastructure facility is 75.02% which is categorized as developed. The development of fisheries production in Blanakan Sub- district, Subang Regency has reached 68.64% with less developed categories, the development of fisheries processing reaches 70.38% with the developed categories, and the development of fisheries product marketing has reached 71.49% with developed categories. For the welfare of the community in the Minapolitan Area, Blanakan Subdistrict is included in the status of family stage prosperous is KS I 10,706 households and for the acceleration of regional development with the fisheries sector is not optimal because of the social aspects of the Minapolitan Area whose education is still low, graduated from elementary school with 21,220 people and no elementary school graduation 12,944 people.